PELATIHAN BAHASA INGGRIS DAN PENGENALAN TEHNOLOGI INFORMASI BAGI REMAJA BENGKONG KOLAM BATAM - Gaguk Rudianto; Zia Hisni Mubarak; Mhd. Johan; Sasa Ani Arnomo; Winda Evyanto; Zakrimal Zakrimal (PUAN INDONESIA, 2022)
This service activity is an activity in the form of training on English Conversation and Introduction to Information Technology for Youth in RT 02 RW 09, Bengkong Sadai Batam which is held at the Gedung Pertemuan RW09 Bengkong.The training held is a multi-disciplinary training or combines several study programs, especially English and Computer Study Programs. The training materials have been prepared in such a way that they are able to at least provide some solutions to the problems of the younger generation that are happening in the current millennial era. These problems include, among other things, teenagers in these neighborhoods do not master English and lack information technology. This training is carried out starting in November 2021 and ending in December 2021 with as many as 5 meetings held regularly. From this training, it is hoped that the training participants will get refreshed knowledge about the application of English and Introduction to Information Technology